2006
DOI: 10.1159/000094378
|View full text |Cite
|
Sign up to set email alerts
|

An Approach for Precise Three-Dimensional Modeling of the Human Inner Ear

Abstract: For further morphological and physiological research, it is vital to establish precise three-dimensional models of the whole inner ear including the details of the membranous components. With the system of a projector and a high-resolution digital camera, 2 complete serial unstained celloidin sections of fresh human temporal bones were digitized as high-resolution images which were then sorted, calibrated, aligned and segmented using the 3D-Doctor software. Finally, 2 precise three-dimensional models of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
15
1
Order By: Relevance
“…The most important one of them was how to align the position of structures in earlier and later pictures precisely. In previous studies, in order to match the contours of the inner ear in consecutive sections, the most common method has been to dig four small holes in the embryo before sections were made and using the four holes to match the sections [5] . But in our case this was not reasonable and we were unable to dig holes in the small-size embryos of the C57BL/6 mouse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important one of them was how to align the position of structures in earlier and later pictures precisely. In previous studies, in order to match the contours of the inner ear in consecutive sections, the most common method has been to dig four small holes in the embryo before sections were made and using the four holes to match the sections [5] . But in our case this was not reasonable and we were unable to dig holes in the small-size embryos of the C57BL/6 mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that using a variety of computerized image processing and reconstruction techniques can reconstruct an anatomically accurate 3-D computer model of the human temporal bone from serial histological sections [4,5] . But compared to the human temporal bone, the adult mouse temporal bone is much smaller and more difficult to reconstruct.…”
Section: -D Reconstruction Of Mouse Inner Ear During Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…3D-Doctor and Amira software (USA) has been applied in medical fields, which has been proven to be stable, high-quality software for three-dimensional reconstruction [7,8].…”
Section: Collection Of Anatomical Cross-sectional Images and Selectiomentioning
confidence: 99%
“…Despite its time consuming nature, many models have been obtained through manual segmentation (Voie and Spelman, 1995;Wada et al, 1998;Ghiz et al, 2001;Li et al, 2006;Lui et al, 2007;Hofman et al, 2009), some also use simple semi-automatic algorithms implemented in "Amira" (Visage Imaging GmbH), a popular 3D reconstruction software Meshik et al, 2009). Lee et al (2010) used not further specifiedmanual and semi-automatic algorithms implemented in another software "Avizo 6" (VSG SAS, Bordeaux, France) of the three scalae in the apical end of the guinea pig cochlea.…”
Section: Introductionmentioning
confidence: 99%